Simulations and global sensitivity analysis of the thermo-hydraulic-mechanical processes in a fractured geothermal reservoir. (15th May 2022) - Mahmoodpour, Saeed; Singh, Mrityunjay; Turan, Aysegul; Bär, Kristian; Sass, Ingo
Abstract: A fractured reservoir can support and sustain long-term geothermal energy extraction operations. The process of injecting cold water to extract hot water from a fractured reservoir result in thermal and poroelastic stress alteration in the rock matrix and the fracture. The thermo-hydro-mechanical (THM) processes govern the efficiency of an enhanced geothermal system (EGS) operation. The THM processes are controlled by various rock and fluid parameters and the initial and boundary conditions of the model set-up. In this paper, we have identified and analyzed 22 parameters. Due to this large number of involved parameters, it is a rigorous process to accurately estimate the relative importance of individual parameters. Thermal breakthrough time, mass flux and overall energy recovery are the three key aspects of operating a geothermal reservoir efficiently and economically. We have performed an extensive sensitivity analysis using the design of the experiments method (Plackett-Burman) and identified key parameters influencing these three key aspects. For a given discrete fracture network, the fracture aperture, the rock matrix permeability, and the wellbore radius are the most influential parameters controlling the thermal breakthrough time, production well mass flux, and overall energy recovery. Accurate estimation of these influencing parameters is important before a field investigation. Highlights: Sensitivity analysis of THM process for geothermal energy extraction is performed. Fracture aperture, rock permeability, and wellbore radius are key parameters. Detailed measurement is required for a limited number of parameters.